The Influence of Jigsaw Technique in Teaching ESP for Graduated Students at College of Physical Education for Women - بان جعفر صادق (physical education and sport sciences college for women/ Baghdad University, 2014)
The current research is an attempt to investigate experimentally the influence of using a jigsaw technique in teaching ESP for graduated student o their speaking achievement. This technique is intended to improve students' speaking skill through providing them with opportunities to choose their material, express information, describe pictures, comment on the information, argument... and giving opinions. The sample of the research is M.A students at College of Physical Education for Women, University of Baghdad of the academic year 2012-2013. It is hypothesized that there are no significant differences between the pre test (includes three observations) and post test (included three observations). To fulfil the aim of the research an experiment has been designed with one group of (20) chosen in purpose from the M.A students. The researcher herself is taught the group. The first course of the study is included three observations. While the second course of the study is applied jigsaw technique with the same group. The experiment lasted four months. In this period, there are six observations. Three observations are in pre tests as well as in the post tests. It has used the observation tool for collecting and scoring the speaking skill of the sample. For the reliability of the observation, it has applied rating sheet, Baker (1989) criteria, recording the observations. After analyzing the results statistically, iIt has been found that there are significant differences between the pre and post tests. This indicates that using jigsaw technique in teaching speaking skill is more effective than using the traditional method. Accordingly the null hypothesize has been rejected. Finally, College of Physical Education are recommended to use a jigsaw technique in teaching speaking skill. And other studies are needed for modern methods and techniques in teaching English language as a foreign language.